Genetic Diversity and Genome Size Variability in the Russian Genebank Collection of Tea Plant [Camellia sinensis (L). O. Kuntze] - Samarina, Lidiia S.; Matskiv, Alexandra O.; Shkhalakhova, Ruset M.; Koninskaya, Natalia G.; Hanke, Magda-Viola; Flachowsky, Henryk; Shumeev, Alexander N.; Manakhova, Karina A.; Malyukova, Lyudmila S.; Liu, Shengrui; Zhu, Juanyan; Gvasaliya, Maya V.; et al. (Frontiers in Plant Science, 2022)
The tea collection of the FRC SSC RAS (Sochi, Maykop in Russia) represents one of the northernmost germplasm comprising a number of locally derived cultivars and ɣ-irradiation mutants. The latter are often characterized by larger genome size, which may lead to better adaptation to biotic and abiotic stress. Such genotypes may be a valuable genetic resource for better adaptability to extreme environmental conditions, which could enable tea cultivation outside global growing regions. Microsatellite markers are often the best choice for genetic diversity analysis in genebank collections. However, their use in polyploid species is questionable because SSR allele dosage cannot be readily determined. Therefore, the efficiency of simple sequence repeat (SSR) and start codon targeted (SCoT) markers was investigated using 43 selected cultivars from the Russian genebank collection derived from mutant breeding and clonal selection. Previously, the increase in genome size was confirmed in 18 mutants within this collection. Despite the presence of polyploid tea genotypes, our study revealed higher efficiency of SSR markers than SCoT markers. Subsequent SSR analysis of the 106 genotypes in the Russian genebank collection revealed three distinct genetic clusters after STRUCTURE analysis. Greater genetic variation was observed within genetic clusters than between clusters, indicating low genetic variation between collections. Nevertheless, the northernmost tea collection exhibited a greater genetic distance from the other two clusters than they did from each other. Close genetic relationships were found between many cultivars with particularly large leaves and mutant forms. Pearson's correlation analysis revealed a significant, moderate correlation between genome size and leaf area size. Our study shows that microsatellite fingerprinting is useful to estimate the genetic diversity and genetic background of tea germplasm in Russia despite polyploid tea accessions. Thus, the results of our study contribute to the development of future tea germplasm conservation strategies and modern tea breeding programs.